Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd000254.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamin and mineral supplements for slowing the progression of age-related macular degeneration

Abstract: Effects of long-term zinc supplementation on plasma thiol metabolites and redox status in patients with age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 46 publications
0
59
0
Order By: Relevance
“…In addition, to our knowledge there is no evidence that patients with early ARMD will benefit from betacarotene supplementation. 19 Based on our findings, we believe that the public should be discouraged from taking beta-carotene supplements to improve vision without a recommendation from their ophthalmologists.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, to our knowledge there is no evidence that patients with early ARMD will benefit from betacarotene supplementation. 19 Based on our findings, we believe that the public should be discouraged from taking beta-carotene supplements to improve vision without a recommendation from their ophthalmologists.…”
Section: Discussionmentioning
confidence: 78%
“…3,4 In brief, we searched the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Group Trials Register) in The Cochrane Library, MEDLINE, SIGLE, EMBASE, National Research Register, AMED and PubMed, reference lists of identified reports, and the Science Citation Index. We contacted investigators and experts in the field for details of unpublished studies.…”
Section: Methodsmentioning
confidence: 99%
“…Trials were selected according to prespecified inclusion criteria. 3,4 Five parameters of trial quality were assessed: allocation concealment, method of allocation to treatment, documentation of exclusions, masking of outcome assessment, and completeness of follow-up. 7 Each parameter of trial quality was graded: A, low risk of bias; B, moderate risk of bias; or C, high risk of bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with low zinc levels have shown reduced lymphocyte proliferation response to mitogens and other adverse alterations in immunity that can be corrected by zinc supplementation . Both zinc and antioxidants delay the progression of age-related macular degeneration (AMD) and vision loss, possibly by preventing cellular damage in the retina (Marshall, 2000;Evans, 2006). Cigarette smoke contains a large number of oxidative compounds.…”
Section: Introductionmentioning
confidence: 99%